India's inequality an uneasy reconciliation with economic growth. [article]. - Zagha, Roberto
"Inequality in India could be much more efficiently reduced through reforms that shrink the costly system of transfers, increase the role of markets in resource allocation, expand infrastructure investments, and improve the delivery of education and health care." -(from the author)